Validation on laboratory simulated optical fibre sensor instrumented bored pile defect using 3D Finite Element Method - Beddelee, A.A.A.M. (Springer Science and Business Media Deutschland GmbH, 2022)
Distributed Optical Fibre Strain Sensing (DOFSS) through Brillouin Optical Time-Domain Analysis (BOTDA) can measure complete (continuous) strain profile and load transfer along a pile shaft. This sensor provides an extra tool to detect the anomalies in the pile behaviours under static load test, such as spikes in strain readings which may indicate the pileâs defect. Laboratory simulation of DOFSS instrumented bored pile has systematically investigated the relationship between the anomality of distributed strain profile in the concrete piles with various typical pile defects at the field including necking, bulging and concrete contamination. The laboratory work has proved that the necking, honeycomb and concrete contamination resulted in strain increment. Conversely, the strain decreases at the rebar lapping area. Hence, a hypothesis of the DOFSS instrumentation in the bored pile able to detect a defect of the pile in terms of geometrical cross-section and material quality (stiffness) was drawn and shall be validated. This paper presented the validation performed by back analysing real field data of DOFSS instrumented bored piles from two selected projects performed by the authors' team utilizing the 3-Dimensional Finite Element Method (FEM). The projects were reported to experience defects after an analysis of the plotted strain profile was made. The defect pile was simulated in the Rocscience 3 and resulted in the same strain profile as measured at the field. Therefore, the presented data justified the discovery and the ability of DOFSS to detect pile imperfection is legit. Â© 2022, Springer-Verlag GmbH Germany, part of Springer Nature.